Karakteristik Tanah Dasar Bekas Likuifaksi Desa Jono Oge Kecamatan Sigi Biromaru Kabupaten Sigi - Basry, Wahiduddin; Hasanuddin, Hasanuddin; Sukmawaty, Dewi; Sholeh, Ahmad (Borneo Engineering : Jurnal Teknik Sipil, 2024)
The 2018 earthquake and liquefaction disaster in Central Sulawesi left significant damage, including in Jono Oge Village, Sigi District. In Jono Oge Village, there was a significant change in the properties of the subsoil. Therefore, in the process of rebuilding the infrastructure, good planning is needed, especially in terms of analyzing the characteristics of the subsoil in the location. This study aims to identify the characteristics of the subsoil in Jono Oge Village. These characteristics include the physical properties of the subsoil obtained through sieve analysis, Atterberg limits, specific gravity of the soil, hydrometer analysis, unit weight (volume), and the mechanical properties of the subsoil obtained from compaction tests (optimum moisture content) and the California Bearing Ratio (CBR) laboratory value. Based on the AASHTO classification, the results of laboratory tests for sample 1 fall into the category of A-1 soil (stone fragments, gravel, and sand), while samples 2 and 3 fall into the category of A-4 soil (silty soil). The mechanical properties of the soil based on specific gravity tests show an average value of 2,66 for sample 1, indicating the presence of gravel and sand grains, while samples 2 and 3 have an average value of 2,59 and 2,58, indicating the presence of organic clay grains. Referring to the Bina Marga specification revision II 2018, this liquefaction soil is suitable for use as subgrade with the results of laboratory CBR tests showing an average value of 16.59% which exceeds the minimum limit of 6%.